Menyelidiki lokalitas: Perspektif sosial budaya dan teknologi (ARTEKS : Jurnal Teknik Arsitektur, 2021)
This edition of ARTEKS: Jurnal Teknik Arsitektur presents a series of the investigation into the locality as an attempt to contribute to the development of architectural knowledge that addresses particular contexts. In architecture, as in many other disciplines, knowledge is developed and transformed through inquiry and investigation, as a means to take a position in relation to the existing knowledge. Knowledge is established through the process of dialectic that contains three parts: the thesis as the originating idea, position, or statement; the antithesis as the opposite or counter-argument to the thesis; and the synthesis as the reconciliation or transformation of those two (Fichte, 1868). Through the continuing process of dialectic, knowledge is not static and limited to what has been known before but is continuously transformed through questioning, arguing, and re-positioning. Research as a form of inquiry and investigation plays an important role in establishing the debate within the discipline (Smith, 2012) to push the boundaries of knowledge.  Architecture as a form of knowledge should be developed through research (Till, 2011), which could be performed through a range of research methods (Groat & Wang, 2013; Lucas, 2016)
Keywords: Lokalitas; Sosial budaya; Teknologi; ARTEKS : Jurnal Teknik Arsitektur